Activating transcription factor 3 modulates the macrophage immune response to Mycobacterium tuberculosis infection via reciprocal regulation of inflammatory genes and lipid body formation. (20th November 2019) - Kumar, Manish; Majumder, Debayan; Mal, Soumya; Chakraborty, Sohini; Gupta, Pushpa; Jana, Kuladip; Gupta, Umesh D.; Ghosh, Zhumur; Kundu, Manikuntala; Basu, Joyoti
Abstract: Infection of macrophages by Mycobacterium tuberculosis elicits an immune response that clears the bacterium. However, the bacterium is able to subvert the innate immune response. Differential expression of transcription factors (TFs) is central to the dynamic balance of this interaction. Among other functions, TFs regulate the production of antibacterial agents such as nitric oxide, pro‐inflammatory cytokines and neutral lipids which are stored in lipid bodies (LBs) and favour bacterial survival. Here, we demonstrate that the TF activating transcription factor 3 (ATF3) is upregulated early during infection of macrophages or mice. Depletion of ATF3 enhances mycobacterial survival in macrophages suggesting its host‐protective role. ATF3 interacts with chromatin remodelling protein brahma‐related gene 1 and both associate with the promoters of interleukin‐12p40, interleukin‐6 and nitric oxide synthase 2, to activate expression of these genes. Strikingly, ATF3 downregulates LB formation by associating at the promoters of positive regulators of LB formation such as cholesterol 25 hydroxylase and the microRNA‐33 locus. ATF3 represses the association of the activating mark, acetyl histone H4 lysine 8 at the promoter of cholesterol 25 hydroxylase. Our study suggests opposing roles of ATF3 in regulation of distinct sets of macrophage genes during infection, converging on a host‐protective immune response.